HUBUNGAN STIGMA DAN DUKUNGAN KELUARGA DENGAN KEKAMBUHAN PADA PASIEN SKIZOFRENIA DI WILAYAH KERJA PUSKEMAS SEI LANGKAI - Marsila, Marsila; Yunaspi, Didi; Fatrida, Dedi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Schizophrenia is a severe mental disorder characterized by disturbances in thinking, emotions, and behavior, and can affect an individual's ability to function socially. Relapse often occurs in schizophrenia patients due to lack of family support and high stigma from the surrounding environment. The purpose of this study was to determine the relationship between stigma and family support with relapse in schizophrenia patients in the working area of the Sei Langkai Community Health Center, Batam City. This study is a quantitative study with an analytical design with a cross-sectional approach. The population of this study were schizophrenia patients who experienced relapse in the working area of the Sei Langkai Community Health Center, with a sample of 43 respondents selected using a simple random sampling technique. The research instrument was a questionnaire on stigma, family support, and relapse that had been tested for validity and reliability. The results of the univariate study showed that most of the stigma was moderate (16 people (37.2%), good family support (23 people (53.5%), and no relapse (25 people (58.1%). Statistical tests using the Chi-Square test showed a significant relationship between stigma and relapse in schizophrenia patients with a p value of 0.001 (<0.05), as well as a significant relationship between family support and relapse in schizophrenia patients with a p value of 0.001 (<0.05). Therefore, it can be concluded that stigma and support have a significant relationship with relapse in schizophrenia patients in the working area of the Sei Langkai Community Health Center, Batam City. Therefore, it is hoped that families and the community can provide optimal support and reduce negative stigma towards schizophrenia patients so that the recovery process can run smoothly.Keywords: Stigma, Family Suport, Relapse, Schizophrenia Patients